Pharmacokinetics and Tissue Distribution of Loratadine, Desloratadine and Their Active Metabolites in Rat based on a Newly Developed LC-MS/MS Analytical Method - Zhang, Yuxin; Lu, Yihua; Wang, Lijuan; Tian, Yuan; Zhang, Zunjian (Drug Research, 2020)
Loratadine (LOR) and its major metabolite, desloratadine (DL) are new-generation antihistamines. The hydroxylated metabolites of them, 6-OH-DL, 5-OH-DL and 3-OH-DL are also active because of their ability to inhibit binding of pyrilamine to brain H1 receptors and a tendency for distributing to specific immune-regulatory tissues. In this study, a new validated LC-MS/MS method to simultaneously quantify LOR, DL, 6-OH-DL, 5-OH-DL and 3-OH-DL in plasma and tissues was established and applied to an investigation of their pharmacokinetics and target-tissue distribution tendency for the first time. Pharmacokinetics parameters in rat were measured and the results suggest that the body’s exposure to active metabolites were much higher than to the prodrug with LOR, but much lower with DL. The tissue distribution study shows that LOR, DL and their active metabolites were widely distributed in the liver, spleen, thymus, heart, adrenal glands and pituitary gland. For immune-regulatory tissues, the concentrations of LOR, DL and their active metabolites in the spleen were much higher than in the thymus, which is related to the spleen, one of the sites where immune responses occur. LOR and its metabolites might inhibit immune-mediated allergic inflammation through the hypothalamic-pituitary-adrenal (HPA) axis. It was also found that the concentration of LOR in the heart was highest after liver and adrenal glands while those of DL, 6-OH-DL and 5-OH-DL in the liver, adrenal glands and spleen were all higher than those in the heart, which suggests that LOR may have a greater tendency to distribute in the heart than its metabolites.
Keywords: drug metabolism; pharmacokinetics; absorption; loratadine; desloratadine; active metabolites; tissue distribution